ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN HARGA POKOK KAMAR HOTEL - Kusnadi Yudha Wiguna; Subianto Subianto; Sayulestari Aprillia (Unitri Press, 2022)
The purpose of this study is to determine the Activity Based Costing (ABC) System in determining the Cost of Hotel Room. The data used are primary data in the form of interviews and secondary data in the form of documentation with data analysis and analytical techniques used are descriptive qualitative. The results of the study obtained that the cost of the traditional system premium type rooms is less than Rp. 381,600 compared to using the ABC system of Rp. 390,905.77 with a difference of Rp. 9,305.77. Traditional system deluxe type rooms are smaller Rp. 306,900 compared to using the ABC system of Rp. 365,919.39 with a difference of Rp.59,019.39. The traditional system triple type room is smaller Rp. 282,600 compared to using the ABC system of Rp. 338,883,03 with a difference of Rp.56,283,03. The traditional system twin type room is smaller Rp. 282,600 compared to using the ABC system of Rp. 319,732.42 with a difference of Rp. 37,132.42. Standard type rooms using the traditional system are smaller Rp. 202,500 compared to using the ABC system of Rp. 311,650.26 with a difference of Rp. 109.150.26.